Efficiency Measurement of Malaysia's Maritime Enforcement Agencies Using Data Envelopment Analysis - Kasmin, Sutarji (2003)
The study is concerned with measuring the degree or amount of efficiency of Malaysia's maritime enforcement agencies in pursuing their objectives. The ideal approach in determining efficiency in non-profit organization is one which will deal with multiple inputs and outputs simultaneously. This study therefore, attempts to broaden the scope of evaluation for the efficiency of non-profit organization in that it takes account all outputs as well as inputs that are required and desirable for effectiveness and allows for simultaneous interaction in their measurement and evaluation. The study addressed the problem of four maritime enforcement agencies that are managed sectorally and functioning independently of one another. Under this system, each agency is established to enforce law and regulations related to its establishment, develops its own organization, manpower and training structures, acquire facilities and assets to meet its own requirement, operate independent budget and financial system, and established its own working culture independent of other organisation. This system is inherent with many weaknesses such as duplication of responsibilities, lack of coordination among enforcement agencies and lack of focus on the economic use of assets. Hence, these agencies are believed to be inefficient to the extent that their operational effectiveness is also affected.